Interpreting personality theories - Bischof, Ledford J. (Harper & Row, Publishers, 1970)
Discusses the theories of Freud, Murray, Jung, Adler, Horney, Moreno, Allport, Rogers, Murphy, Sheldon, Cattell, Eysenck, Lewin, Mowrer, Maslow, Kelly, Erikson, Sullivan, and Fromm.